Comparing Rotational Stability of Clareon and Eyhance Toric IOLs in a Real-World Setting - Connell B; LaHood B (Clinical Ophthalmology)
Ben Connell,1,2 Ben LaHood3,4 1Eye Surgery Associates, Melbourne, VIC, Australia; 2Corneal Clinic, Royal Victorian Eye and Ear Hospital, Melbourne, VIC, Australia; 3Adelaide Eye and Laser Centre, Adelaide, SA, Australia; 4University of Adelaide, Adelaide, SA, AustraliaCorrespondence: Ben Connell, Eye Surgery Associates, 2/232 Victoria Pde, East Melbourne, VIC, 3002, Australia, Email benconnell@outlook.com.auBackground: The Eyhance Toric intraocular lens (IOL) builds upon the Tecnis Toric platform, initially associated with considerable post-operative rotational instability. Version 2, the Eyhance Toric IOL has been modified to enhance rotational stability. This study evaluates the post-operative rotational stability of the Eyhance Toric IOL compared to the Clareon Toric IOL, recognized for its stable performance.Methods: Patients undergoing cataract surgery received either the Eyhance or Clareon Toric IOLs. Placement was guided by the Barrett Toric Calculator at baseline (P0). IOL stability, uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), and refractive astigmatism were assessed at 6– 24 hours (P1) and 3 weeks to 6 months (P2) post-operatively. IOL rotational measurements were recorded at each interval.Results: The study included 187 patients (median age: 74 for Clareon, 79 for Eyhance, p = 0.004). No significant differences were found in UDVA, CDVA, or refractive astigmatism at P2. Median rotation from P0 to P1 (3.0 vs 4.0 degrees, p = 0.091) and P0 to P2 (1.0 vs − 0.5 degrees, p = 0.482) were not statistically different. However, the Clareon IOL showed less rotation between P1 and P2 (0.0 vs 1.0 degrees, p = 0.049). Absolute rotation from P0 to P1 (4.0 degrees), P1 to P2 (1.0 vs 2.0 degrees, p = 0.064), and P0 to P2 (4.0 vs 3.5 degrees, p = 0.095) were comparable.Conclusion: The Eyhance Toric IOL demonstrated comparable rotational stability and visual outcomes to the Clareon Toric IOL. Modifications in the Eyhance design have successfully improved its rotational stability, positioning it as a viable alternative to the Clareon Toric IOL in clinical practice.Keywords: Eyhance toric, Tecnis toric, Clareon toric, rotational stability